A War Remembered: People Gather at Moving Wall to Honor Vietnam Dead - Valdosta Daily Times; Spires, Shelby G. (Valdosta Daily Times, vol. 90, no. 149. March 16, 1995., 1995)
Newspaper article from the Valdosta Daily, March 16, 1995 regarding the Moving Wall Vietnam Memorial.
1 electronic record (PDF), 1 pages. 2802338 bytes.
Keywords: Valdosta Daily Times (Valdosta; Ga.); Lowndes County (Ga.); Valdosta (Ga.); Vietnam War (1961-1975); War memorials